Key figures on the enlargement countries - 2014 edition (Luxembourg, 2014)
"This extensive pocketbook on enlargement countries covers the years 2002 to 2012 and contains tables and graphs on demography, education, social conditions and labour force, national accounts, finance and prices, agriculture, energy, industry, construction and services, transport, communications and information society, as well as external trade, research and development and environment. A short commentary on the data and methodological notes are also included. "